Criminal Law Policy Regarding Scientific Crime Investigation in Terrorism Crimes - HM, Safri; Utomo, Laksanto; Hakim, Lukman (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Terrorism is one of the legal phenomena that occurs in society, where the acts of terrorism known by the public are basically only around bombings and shootings carried out by perpetrators of terrorist crimes, but in fact the crime of terrorism itself consists of various forms of actions as regulated in Law Number 5 of 2018 concerning the Prevention and Eradication of Criminal Acts of Terrorism Financing. From the terrorism law, the types of roles of perpetrators of terrorist crimes can be identified, both as executors and as financiers, including executors and financiers. Extraordinary efforts are needed in preventing and prosecuting terrorism, one of which is by utilizing SCI ( Scientific Crime Investigation ), which has a broad scope in the use of technology and science, and is currently proven to be able to help various human activities including in maximizing investigative and investigative efforts by the Indonesian National Police. However, the legal regulations related to SCI itself within the scope of criminal procedural law in Indonesia are still quite limited, and do not yet include regulations at the level of statutory regulations such as in the Criminal Procedural Law in Indonesia, so that in this paper will be explained the importance of SCI being included in the Criminal Procedural Law in Indonesia and its use in the investigation and prosecution of criminal acts of terrorism in order to maximize efforts to prevent and prosecute criminal acts of terrorism.